Kinematic motion of the windmill softball pitch in prepubescent and pubescent girls - Oliver, G. D.; Dwelly, P. M.; Kwon, Y.-H. (The Journal of Strength and Conditioning Research, 2010)
This study examined the joint motions and movement patterns of the kinetic chain in the ballistic skill of performing the windmill pitch. Seventeen healthy girls who were currently playing competitive fast-pitch softball volunteered for the study. Subjects were instructed to perform 5 successful fastball windmill style deliveries. We selected 1 pitch for analysis based on the velocity, accuracy, and subjects' input. Kwon3D motion analysis package (Visol., Inc., Seoul, Korea), with 6 digital camcorders placed at 60° apart was used for analysis. Raw data were interpolated using a frequency of 60 Hz and then smoothed using Butterworth low-pass second-order filter with a fixed cut-off frequency of 6 Hz. The subjects were divided into groups based on skill level: novice, intermediate, and advanced. Sequential progression of kinematic variables that resulted in increased throwing velocity and the contribution each segment (upper arm, forearm, and hand) possessed toward ball velocity with descriptive statistics and path analysis were assessed. There was evidence of sequentiality among the arm segments in the intermediate and advanced groups. The patterns of the shared positive contributions made by each of the limb segments were similar among the 3 groups of participants. The novice group tended to rely on more of the upper arm and forearm than the other 2 groups. From this study, it is evident that all emphasis should not be placed on the shoulder, but training and conditioning methods should focus on the entire kinetic chain including the torso and the full arm segment, not just the shoulder in an attempt to gain the greatest velocity while performing the 360° arc of the windmill softball pitch.